Mass customization and testing of braces using additive manufacturing. (2022) - Leong, K.F.; Teng, P.S.P.; Er, B.H.; Tee, C.H.
Abstract: Current methods to fabricate customized braces typically require a mold of the foot and often require casts to be pre-manufactured or milled from a solid block. This is time consuming and expensive. However, additive manufacturing opens opportunities for mass customization. Selected regions of customized protection or varying properties for the joint range of motion for braces is also possible with 3D printing solutions. This study explored the use of additive manufacturing for the mass customization of braces, using the ankle brace as an illustration. This paper showcases the methodology of using a glass scanner to obtain individual biomechanics data; incorporating personalized data in a pre-designed brace template; designing mass customized braces using Rhinoceros 6 Grasshopper; and manufacturing of the ankle brace using fused deposition modelling. Initial tests on the dynamometer showed that maximum ankle inversion angle was reduced by almost a third, as compared to barefoot conditions. This potentially will significantly reduce ankle lateral sprain injury risks at ankle inversion positions especially beyond functional range of motion and successfully demonstrated the possibility of using 3D printing solutions for similar mass customized applications.